Formation and deformation of hyperextended rift systems: Insights from rift domain mapping in the Bay of Biscay‐Pyrenees. Issue 7 (3rd July 2014) - Tugend, J.; Manatschal, G.; Kusznir, N. J.; Masini, E.; Mohn, G.; Thinon, I.
Abstract The Bay of Biscay and the Pyrenees correspond to a Lower Cretaceous rift system including both oceanic and hyperextended rift domains. The transition from preserved oceanic and rift domains in the West to their complete inversion in the East enables us to study the progressive reactivation of a hyperextended rift system. We use seismic interpretation, gravity inversion, and field mapping to identify and map former rift domains and their subsequent reactivation. We propose a new map and sections across the system illustrating the progressive integration of the rift domains into the orogen. This study aims to provide insights on the formation of hyperextended rift systems and discuss their role during reactivation. Two spatially and temporally distinct rift systems can be distinguished: the Bay of Biscay‐Parentis and the Pyrenean‐Basque‐Cantabrian rifts. While the offshore Bay of Biscay represent a former mature oceanic domain, the fossil remnants of hyperextended domains preserved onshore in the Pyrenean‐Cantabrian orogen record distributed extensional deformation partitioned between strongly segmented rift basins. Reactivation initiated in the exhumed mantle domain before it affected the hyperthinned domain. Both domains accommodated most of the shortening. The final architecture of the orogen is acquired once the conjugate necking domains became involved in collisional processes. The complex 3‐D architecture of the initial rift system may partly explain the heterogeneous reactivation of the overall system. These results have important implications for the formation and reactivation of hyperextended rift systems and for the restoration of the Bay of Biscay and Pyrenean domains.